Implementation of the 5S Method in Increasing Work Efficiency at a Manpower Services Company in Gresik - Rohmafika, Delaega Hilmalillah; Author , Rahmat Agus Santoso (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This research aims to analyze the application of the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) in increasing work efficiency at employment service company, a company operating in the service sector. The research method used is a qualitative approach with data collection through observation, interviews and document analysis. The research results show that even though 5S has been implemented, the level of implementation still varies. Seiri and Seiton elements show value that needs to be improved, while Seiso and Seiketsu have been implemented well. The main obstacles faced include employees' lack of understanding of the importance of 5S and resistance to change. As a solution, it is recommended that management conduct regular training and outreach regarding the 5S method and implement a periodic audit system to ensure consistency of implementation. It is hoped that this research can contribute to increasing work efficiency at employment service company and become a reference for other companies in implementing the 5S method